2016
DOI: 10.1038/mtna.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TSLP With shRNA Alleviates Airway Inflammation and Decreases Epithelial CCL17 in a Murine Model of Asthma

Abstract: Airway epithelium defends the invasion from microorganisms and regulates immune responses in allergic asthma. Thymic stromal lymphopoietin (TSLP) from inflamed epithelium promotes maturation of dendritic cells (DCs) to prime Th2 responses via CCL17, which induces chemotaxis of CD4+ T cells to mediate inflammation. However, few studies have investigated the regulation of epithelial CCL17. In this study, we used shRNA against TSLP to clarify the role of TSLP in the airway inflammation and whether TSLP affects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
(52 reference statements)
1
10
0
1
Order By: Relevance
“…As an epithelium‐derived cytokine, TSLP represents a master switch at the interface between environmental allergens and pulmonary allergic immunologic responses . TSLP was verified to be a sufficient and necessary factor for the initiation of allergic airway inflammation by contacting lung DCs . Thus, we further detected TSLP expression in lung after HDM stress.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…As an epithelium‐derived cytokine, TSLP represents a master switch at the interface between environmental allergens and pulmonary allergic immunologic responses . TSLP was verified to be a sufficient and necessary factor for the initiation of allergic airway inflammation by contacting lung DCs . Thus, we further detected TSLP expression in lung after HDM stress.…”
Section: Resultsmentioning
confidence: 76%
“…33 TSLP was verified to be a sufficient and necessary factor for the initiation of allergic airway inflammation by contacting lung DCs. 34 Thus, we further detected TSLP expression in lung after HDM stress. TSLP mRNA expression in lung was upregulated significantly in the HDM stressed ITGB4 −/− mice compared with control mice (Fig.…”
Section: Increased Expression Of Tslp Was Induced By Activation Of Nfmentioning
confidence: 92%
“…Interestingly, it has been reported that alveolar DC-derived CCL17 is critical for airway inflammation 169 , 170 and CCL17 airway expression correlates with asthmatic disease severity. 171 , 172 In our view these data warrant a detailed study examining the role of the GM-CSF/CCL17 axis in asthma, with CCL17 being a potential target for treating allergic disease and/or a biomarker for patient selection.…”
Section: Gm-csf In Diseasementioning
confidence: 93%
“…The specific enhanced expression of TSLP in airway epithelial cells results in initial CD4 + T lymphocyte proliferation and Th2 cell differentiation (38). Conversely, targeting TSLP with short hairpin RNA or antibodies, alleviates airway inflammation and decreases epithelial CCL17 in a murine model of asthma (51,52).…”
Section: Functional Properties Of Chemokines and Associations Betweenmentioning
confidence: 99%